2021
DOI: 10.1002/wwp2.12054
|View full text |Cite
|
Sign up to set email alerts
|

Empirical analysis of the impact of urbanization on groundwater quality within the slums of Accra, Ghana

Abstract: A significant proportion of city dwellers in Ghana reside in slums where groundwater is the major source of water for domestic uses. This study examined the quality of groundwater from boreholes (seven) and hand‐dug wells (13) in five major slums in the city of Accra, Ghana. Water samples were tested for a total of 27 microbial and physicochemical contaminants at the central laboratory of the Ghana Water Company Limited. Overall, the water quality in the slums was poor as most of the parameters tested did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…However, due to price, households are unlikely to use such sachet water for other household activities such as cooking and bathing. A recent study in five slums in Accra, (Nima, Sabon Zongo, Chorkor, Jamestown, and Abokobi-Pantang) which includes slums both within our treatment area and downstream, found that groundwater was used for cooking (Ketadzo et al, 2021). Households who lack access to piped water may also lack access to personal bathing facilities; one study in Accra estimated that 18% of households who used sachets for drinking water used local rivers as their primary bathing facilities; a further 30% use 'open sources' (Stoler et al, 2012).…”
Section: Underlying Mechanismsmentioning
confidence: 92%
“…However, due to price, households are unlikely to use such sachet water for other household activities such as cooking and bathing. A recent study in five slums in Accra, (Nima, Sabon Zongo, Chorkor, Jamestown, and Abokobi-Pantang) which includes slums both within our treatment area and downstream, found that groundwater was used for cooking (Ketadzo et al, 2021). Households who lack access to piped water may also lack access to personal bathing facilities; one study in Accra estimated that 18% of households who used sachets for drinking water used local rivers as their primary bathing facilities; a further 30% use 'open sources' (Stoler et al, 2012).…”
Section: Underlying Mechanismsmentioning
confidence: 92%
“…Despite these shortfalls, not much have been done to fully assess the quality of self-supply water sources in the coastal areas of Ghana. Most work on the subject is limited to small communities and, in rare cases, districts and regions [ [23] , [24] , [25] , [26] , [27] , [28] ]. There is currently no broad assessment of groundwater that encompasses the entire coastal areas of Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, indices such as the WQI and NPI that provide an overall clear picture and easy-to-understand information on self-supply water source have found limited use in the these areas. Furthermore, some studies have reported the contamination of groundwater sources in coastal areas with heavy metals [ 24 , [29] , [30] , [31] , [32] ]. However, the assessment of the health risks posed by heavy metals in the coastal region regarding drinking water from groundwater sources is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Very little attention is paid to monitoring the fate of drinking water after the collection point, whereas little or no water is consumed at the collection point. The monitoring of the quality of drinking water throughout its chain must be taken into account to ensure the safety of consumers (Cunha, 2020; Fakeha & Ajai, 2021; Ketadzo et al, 2021; Lémonla, 2020). The provision of drinking water in the city of Dschang, as in most medium‐sized cities in sub‐Saharan Africa and in rural areas, generally requires regular movement of people between their homes and the point of collection (standpipe, spring, borehole, well, or river).…”
Section: Introductionmentioning
confidence: 99%